Pengembangan Sistem Informasi Support and Maintenance Berbasis Web pada Pengadilan Negeri Makassar Kelas IA Khusus - M Syahid Nur Wahid; Kelvianto Pratama Harum; Muhammad Alif Leo; Putri Nandasari; Andi Muh Achyar AM (Progressive Information, Security, Computer, and Embedded System, 2023)
Makassar Class IA Special District Court is a first-level judicial institution located in Makassar City, South Sulawesi. This institution uses electronic devices and computers in its daily operations. However, the complaint system and electronic and computer processing still use the conventional method of manually recording and reporting complaints made. To overcome these problems, a "support and maintenance" information system was developed to make it easier for IT staff to manage incoming complaints to the IT department. The development of this information system uses the Waterfall model as its development method. The research method was carried out using several methods, namely observation and interviews to see and know directly the handling of complaints in the IT section of the Makassar District Court, as well as conducting a literature review of relevant readings related to research. The result of this research is a Web-based “Support and Maintenance” Information System.